The Paris detective : three detective Luc Moncrief thrillers - Patterson, James, 1947-; DiLallo, Richard; Patterson, James, 1947-; Patterson, James, 1947-; Patterson, James, 1947- (2021)
A new bind-up with three exciting thrillers featuring NYPD Detective Luc Moncrief, a Paris detective who's about to learn that NYC is a whole other ballgame in the world of crime. French Twist: Gorgeous women are dropping dead at upscale department stores in New York City. Detective Luc Moncrief and Detective Katherine Burke are close to solving the mystery, but looks can be deceiving. French Kiss: Very handsome and charming French detective Luc Moncrief joined the NYPD for a fresh start, but someone wants to make his first big case his last. Welcome to New York. The Christmas Mystery: In the heart of the holiday season, priceless paintings have vanished from a Park Avenue murder scene. Now, dashing French detective Luc Moncrief must become a quick study in the art of the steal, before a coldblooded killer paints the town red. Merry Christmas, Detective.
French Kiss -- The Christmas Mystery -- French Twist.
"Three Detective Luc Moncrief thrillers."
Previously published by Little, Brown as part of the BookShots series, in 2016 (French kiss, and The Christmas mystery) and 2017 (French twist).
Keywords: Murder -- Fiction; Art thefts -- Fiction; Murder -- Investigation -- Fiction; Art thefts -- Investigation -- Fiction; French -- New York (State) -- New York -- Fiction; FICTION / Thrillers / Suspense; FICTION / Mystery & Detective / Police Procedural; FICTION / Crime; Art thefts; Art thefts -- Investigation; French; Murder; Murder -- Investigation; New York (N.Y.) -- Fiction; New York (State) -- New York; Suspense fiction; Mystery fiction; Short stories; Action and adventure fiction; Detective and mystery fiction; Fiction; Short stories; Thrillers (Fiction); Thrillers (Fiction); Detective and mystery fiction; Short stories; Action and adventure fiction